2016
DOI: 10.18280/ijht.340421
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heat Recovery and Recovery Efficiency of a Seasonal Thermal Energy Storage System in a Moist Porous Medium

Abstract: Thermal energy storage has received a great interest by researchers and industrials as part of designing new systems able to store and deliver thermal energy efficiently for long periods, especially in regions characterized by important solar energy potential. The aim of this preliminary work is to simulate the performance of a novel seasonal heat storage system dedicated to store heat in the ground during hot period then to recover it during cold period. The system investigated herein is a ground heat exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…(5) Entransy of supply water The Entransy of the supply water is defined by Equation (18). Space heating can be expressed using Equation (19).…”
Section: Performance Evaluation Indexesmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) Entransy of supply water The Entransy of the supply water is defined by Equation (18). Space heating can be expressed using Equation (19).…”
Section: Performance Evaluation Indexesmentioning
confidence: 99%
“…The results indicated a thermal recovery ratio of less than 67% and different temperature distributions under the three modes. Dada [19] simulated a novel seasonal heat-storage system dedicated to storing heat in the ground during the hot period and then recovering it during the cold period. This approach led to a remarkable increase in temperature levels as well as heat-energy recovery efficiency, which increased from 41% to 71%.…”
Section: Introductionmentioning
confidence: 99%
“…Their study pointed out that the triple helix heat exchanger was better than the other configurations. Dada et al (2016) simulated several case studies with different types of hot fluid carrier, and indicated that the effect of pure water as circulating fluid was better than that of ethylene glycol and gasoline. Kong et al (2017) analyzed the thermal performance of a set of buried vertical U-tubes designed with different petals for ground-source heat pump and investigated different influential factors of thermal response.…”
Section: Introductionmentioning
confidence: 99%